A Lagrangian study of upwelled waters in the Northern Arafura Sea. Issue 1 (December 2020) - Nurfitri, S; Basit, A; Putri, M R; Pätsch, J; Pohlmann, T
Abstract: The Arafura Sea is a relatively shallow water basin (less than 200 m) which is subjected to monsoonal winds and affected by the Banda Sea circulation. During the southeast monsoon (May to September) there is evidence of upwelling in this region which is indicated by the cooler SST (Sea Surface Temperature) and elevated chlorophyll concentration, especially at the coast of Papua (northern Arafura Sea). In order to address the origin of the upwelled waters masses, a numerical study using Lagrangian particles was utilized. The model was run backward in time to trace the trajectory of the particles arriving at the northern Arafura Sea, particularly in the upper 50 meters. Each particle was traced backward for three months with the arrival date August 31, 2014, as it is representative for an upwelling month. By this experiment we can identify the origin of the particles on June 1, including their depth, which arrive in the northern Arafura Sea. The daily velocity fields of the 3-D model HAMSOM (HAMburg Shelf Ocean Model) application to the Banda and Arafura Sea for 2014 were used to force the Lagrangian particle-tracking experiment. In general, 76.2% (62%) of particles arriving in 2.5 m (22.5 m) depth, originated from the upper 50 m of the Ceram and Banda Sea. In addition, particles originating from the depth interval 50-100 m contribute 19.6% (26.8%) to the number of particles arriving in 2.5 m (22.5 m) depth. On the other hand, for particles arriving in 47.5 meter depth 46% are originating from the upper 50 m of the southeastern Arafura Sea and 42% from a depth below 100 m of the eastern Banda Sea.